2017
DOI: 10.18203/2320-1770.ijrcog20170385
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing Janani Suraksha Yojana utilization in a Northern city of India

Abstract: Background: Janani Suraksha Yojana (JSY) was launched by Government of India with an objective of increasing institutional delivery. After years of operationalization in the Union territory of Chandigarh, no studies have documented the extent of its utilization and in-turn, effectiveness of its implementation. The aim and objectives of the study was to ascertain the extent of utilization of JSY scheme and to explore the factors influencing its uptake.Methods: It was a community based cross-sectional mixed meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…9 Difficulty in arranging documents has also been the key issue in West Bengal as reported in his study by Santra et al 17 Residents of Chandigarh added another issue to this list of problems which was the low amount of benefit in the scheme which was demotivating while accessing it. 18 This issue was also reported in a qualitative multi-centric study from three states (Uttar Pradesh, Madhya Pradesh and Jharkhand) in India. 19 In the current scenario of inflation and rising price of essential commodities, the monetary incentive seems low from the perspectives of poor population residing in urban areas.…”
mentioning
confidence: 68%
“…9 Difficulty in arranging documents has also been the key issue in West Bengal as reported in his study by Santra et al 17 Residents of Chandigarh added another issue to this list of problems which was the low amount of benefit in the scheme which was demotivating while accessing it. 18 This issue was also reported in a qualitative multi-centric study from three states (Uttar Pradesh, Madhya Pradesh and Jharkhand) in India. 19 In the current scenario of inflation and rising price of essential commodities, the monetary incentive seems low from the perspectives of poor population residing in urban areas.…”
mentioning
confidence: 68%
“…But the study in Chandigarh revealed dissatisfaction among the beneficiaries that JSY needed too much paper work and it would have been better if money could be disbursed before delivery. 27 We found gross variety in terms of the concerned person disbursing cash. It seemed, whoever was found capable of handling money had been entrusted with doing so.…”
Section: Discussionmentioning
confidence: 84%
“…Shortage of dedicated, skilled staff to handle the record, with or without computers, has been documented and it is expected that once they are placed in proper positions; things would improve. 27,33 As reported, information about the scheme was fairly extensive in the districts surveyed. It was communicated where the beneficiaries were possibly contacted, both through inter-personal conversation as well as through various mass approaches.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations